ALTERNATIVE CLASSIFICATION FOR ELEMENTARY SCHOOL LIBRARIES: A NARRATIVE LITERATURE REVIEW - Boby Prabowo; Wiwit Ratnasari (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2025)
This study aims to review alternative classification systems that can replace the Dewey Decimal Classification (DDC) in elementary school libraries, especially since the Indonesian National Library Regulation No. 4 of 2024 mandates DDC as the required system. The main issue discussed is the incompatibility of DDC with the cognitive and literacy development levels of young users. Using a narrative literature review method, eight relevant studies were analyzed and grouped into four categories of alternative classification systems: visual (color and symbol-based), interest-based, culturally-based, and locally contextualized systems. Findings indicate that alternative classification systems are more inclusive, intuitive, and aligned with how children perceive and interact with information. Visual systems facilitate independent searching and boost reading interest, while interest- and culture-based systems enhance emotional engagement. Locally contextualized systems allow school libraries to adapt to real-world needs. Based on these findings, the study recommends that the National Library provide greater flexibility and innovation opportunities in classification for school libraries, instead of enforcing a single, universal model. Classification systems should be adaptive and centered on students' needs, enabling school libraries to serve as meaningful, engaging learning spaces.